Bone Mineral Density Differences in Hip Fractures of the Elderly - Songviroon, MD, MPH, Surat (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To evaluate the differences in bone mineral density (BMD) between the fracture and non-fracture sides in cases of femoral neck and intertrochanteric fractures in elderly. Methods: A cross-sectional study in elderly patients admitted to Maharat Nakhonratchasima Hospital between March 1, 2012 and September 30, 2012. Each had a diagnosis of femoral neck or intertrochanteric fracture. After applying inclusion and exclusion criteria, one hundred patients were included. All answered the fracture risk assessment tool. BMD was measured by Dual energy X-ray absorptiometry prior to surgery. Data was analyzed statistically. Results: Demographic data from the fracture groups, mean age, and body mass index displayed no statistical differences. BMD measurements were higher on the fracture side than on the non-fracture side and statistically different in nearly all areas of the hip. BMD measurements produced statistical differences in some areas when comparison was made between fracture groups, and between genders. The BMD in males was not statistically different between the femoral neck and intertrochanteric fracture groups, and between the fractured and non-fractured sides. Conclusion: Overall the BMD was statistically different between the fracture and non-fracture sides. In addition, the BMD was not statistically different between the femoral neck fracture and intertrochanteric fracture groups in some areas.